Adsorption of Reactive Dyes from Wastewater Using Cationic Surfactant-modified Coffee Husk Biochar: DOI: 10.32526/ennrj.18.1.2020.03 - Kosaiyakanon, Chatsuda; Kungsanant, Suratsawadee (Environment and Natural Resources Journal, 2019)
A solid agricultural waste, coffee husk, was applied as an adsorbent for reactive dye-polluted wastewater treatment. Coffee husk biochar was pyrolyzed at 450 °C and then chemically activated using 50% ZnCl2 solution. The surface of activated coffee husk biochar was modified using a cationic surfactant, Cetyltrimethylammonium bromide (CTAB), to create CTAB-modified coffee husk biochar (MCH), to improve reactive adsorption of anionic dyes from synthetic wastewater. The selected reactive dyes were reactive yellow 145 (RDY145), reactive red 195 (RDR195), and reactive blue 222 (RDB222). The adsorption kinetics fit well using a pseudo-second order model for all three dyes. The adsorption isotherms matched well with the Langmuir model . The removal efficiency of RDY145 (83.7%) was the highest, followed by RDR195 (71.1%) and RDB222 (59.6%). The amount of RDY145 adsorbed by MCH was about 9-fold that adsorbed by conventional activated carbon. Additionally, the solution pH had no effect on reactive dye removal efficiency using MCH.